Macau : a backdoor access to China : 16th-17th centuries - Pinto, Paulo Jorge de Sousa (2014)
Paper draft presented to the International Conference Patterns of Early Asian Urbanism, Leiden, International Institute for Asian Studies / Leiden University, 12 November 2013